Analisis Kesulitan Belajar Operasi Hitung Campuran pada Siswa Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the types of student learning difficulties in solving mixed arithmetic operations based on the Newman Error Analysis (NEA) approach. This research uses a descriptive qualitative approach with literature study techniques on national scientific articles published between 2020 and 2025. The data were analyzed based on five categories of errors according to NEA, namely reading errors, comprehension errors, transformation errors, process skill errors, and coding errors. The results showed that students experienced all types of errors, with transformation and process skill errors as the most dominant types. Factors causing the errors include weak mathematical literacy, lack of understanding of basic concepts, low motivation to learn, and limited contextual and interactive learning strategies. The findings recommend the need for the use of NEA-based diagnostic approaches in mathematics learning as well as the integration of visual learning media to strengthen students' understanding of the concept of mixed arithmetic operations.